Additional steps in mechanical recyling of PET - Mancini, Sandro Donnini [UNESP]; Saide Schwartzman, Jonas Age [UNESP]; Nogueira, Alex Rodrigues [UNESP]; Kagohara, Dennis Akira [UNESP]; Zanin, Maria (Elsevier B.V., 2010)
This study presents the laboratory scale results of an extra step in Poly (ethylene terephthalate) - PET mechanical recycling (grinding, washing, drying and reprocessing): a chemical washing after the conventional one. Cooking oil PET bottle flakes were washed in water and then subjected to a reaction with an aqueous solution of sodium hydroxide 5 M at 90 degrees C for 10 min (chemical washing). After rinsing and drying, the flakes were characterized by thermogravimetry, gas chromatography and elemental analysis tests. The results indicated that the chemically washed material had higher purity than PET washed only with water: 99.3% and 96.7%, respectively, which undoubtedly implies properties, applications and prices closer to those of virgin resin. The production of purified terephthalic acid (TPA) from the chemical washing residue was optimized and reached a purity of 99.6%. Despite the results, the use of chemically washed PET and of TPA obtained is not recommended for direct contact with food, since they still contain some impurities. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: PET recycling; Polyethylene terephthalate; Terephthalic acid; Chemical washing